TEOLOGI AL MA’UN: ANALISIS KONTRIBUSI PEMIKIRAN EKONOMI ISLAM DALAM PENYEBARAN KEBAIKAN - Idrus, Ali; Haezah Fahriah, Putri; Gunawan, Agus; Fatma Kartika, Rini (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2025)
This study aims to examine the contribution of Islamic economic thought in spreading goodness by referring to Surah Al-Ma'un in the Quran. This research uses a qualitative approach with library research methods. The results show that the principles of Islamic economics contained in Surah Al-Ma'un can be implemented in the modern economic context to enhance social welfare and fair wealth distribution. Surah Al-Ma'un also emphasizes the importance of good deeds of a social nature in daily life. Keyword: Islamic economics, Surah Al-Ma'un, kindness, social welfare, wealth distribution.